PENGARUH CORPORATE GOVERNANCE, PROFITABILITY, DAN FIRM SIZE TERHADAP TAX AVOIDANCE - Gunawan, Dave Christopher; Ngadiman, Ngadiman (Jurnal Paradigma Akuntansi, 2023)
This study aims to determine the effect of independent commissioners, audit committees, and profitability and firm size on tax avoidance. The population in this study are LQ45 index companies listed on the Indonesia Stock Exchange in 2017-2019. The source of the data used is secondary data from a third party that has been published to serve as a sample in the study. Sampling in this study using purposive sampling method, with a sample of 19 companies with a total of 57 data for 3 years. The data was processed using the IBM SPSS version 25 program. The results of the study found that profitability had an effect on tax avoidance, while independent commissioners, audit committees and firm size had no effect on tax avoidance.